Examining the Role of Well Being in the Marketing Discipline - Perrewé, Pamela L. (Research in Occupational Stress and Well Being Ser., 2019)
Volume 17 of Research in Occupational Stress and Well Beingis focused on the stress and well-being related to the marketing discipline. This volume is focused on the connections between employee stress, health, and well-being as it relates to marketing; sales; customers.